BANK’S PROFITABILITY IN INDONESIA: CASE STUDY OF ISLAMIC BANKS PERIOD 2008-2012 - Faiza Husnayeni Nahar (Universitas Muhammadiyah Yogyakarta, 2017)
Islamic banking is industry sector that contributes to influence the country’s economic growth. As it is necessary to control the quality of bank performance, being banking regulator, Bank Indonesia has responsibility to assess the financial performance of the banks, among which is to see the level of profitability by using Return on Assets (ROA) ratio. The aim of this study is to empirically test a model that links factors such as inflation, Gross Domestic Product (GDP), Capital Adequacy Ratio (CAR), Financing Deposit Ratio (FDR), Non Performing Financing Ratio (NPF) and Operating Expenses over Operating Income (BOPO) to profitability of Islamic Banks in Indonesia from January 2008 to December 2012. This study use panel data of Islamic banks from monthly financial statement data published by Bank Indonesia. The empirical findings of this paper suggest that inflation, GDP, NPF are found statistically positive significant to bank profitability while CAR, FDR and BOPO have negative sign and statistically significant to bank profitability. Since society prefers to do transaction such as saving and invest money with bank which has good performance. It indirectly contributes to increase the Indonesian economic growth.